195=275-275p
-275 -27
-80=-275p
You do -80 divided by -175 which is 0.45 and your answer is C45%.
1st:x
2nd x+2
3rd: x+4
(x)+(x+2) = 3(x+4)-31
distribute
2x+2 = 3x+12-31
2x+2 =3x-19
subtract 2x from each side
2 = x-19
add 19 to each side
21 =x
Answer: 21,23,25
First subtract the two numbers:
8 - 5 = 3
Now divide this to the original:
3 / 5 = 0.6
Multiply by 100:
0.6 * 100 = 60%
Answer:
-437
Step-by-step explanation:
x=3,y=13,z=5
12x-3y4x-z
12(3)-3(13)(4)(3)-5
36-468-5
-437
Answer:
Step-by-step explanation:
Given that,
y=x+2 equation 1
2x-y=-4 equation 2
This is a simultaneous equation.
Substitute equation 1 into equation 2
2x-y=-4. Since y=x+2
2x-(x+2) = -4
2x-x-2 = -4
x-2 = -4
x = -4+2
x = -2
Also from equation 1
y=x+2
Since x=-2
y=-2+2
y=0
Then, solution (x, y) = (-2,0)